Perkembangan Urban Sprawl Kota Semarang pada Wilayah Kabupaten Demak Tahun 2001-2012 - Reni Mujiandari (Jurnal Wilayah dan Lingkungan, 2014)
Limited land resulted city expansion towards the periphery by urbanization. Sub-urban area is still depends on the city core, which is known as urban sprawl (Soetomo, 2009). Urban sprawl in Greater Semarang passed the administrative boundaries, as example in Demak District. The purpose of study is to assess urban sprawl in Greater Semarang (a case in Demak District). In this study, urban sprawl defined in two dimensions, physical and non physical dimensions. Physical dimensions include land use, building density, building function and the level of accessibility. Non- physical dimensions include population density and population of agricultural livelihoods. Urban sprawl in study area during 2001-2012 has been increased 498.685 ha (32.23 % ) which consists of the change from urban sprawl into non-urban sprawl 488.278 ha and changes of non-urban sprawl into urban sprawl 986.963 ha. Development of sprawl has a combination of ribbon development and leapfrog development. Area with distance of 7.5-10 km from the center of Semarang City (ring 1) is the largest growth of urban sprawl. This shows that the distance to the city center to be one of the factors that influence sprawl. Direction of development of new residential is needed to integrated with other existing settlement. Another policy that needs to be considered is the provision of mass transportation facilities and infrastructure so that people living in urban sprawl areas do not need to use a personal vehicle to go to work or to the center of Semarang.